The Effect of Health Worker Performance and Loyalty On Patient Satisfaction Through Service Quality as An Intervening Variable on BPJS Patients At Tamalate Health Center Makassar City - Jayadie, Ahmad; Syamsuddin, Syamsuddin; Hardi, Hardi (Universitas Wiralodra, 2024)
Puskesmas and BPJS are two health service support facilities that are closely related and cannot be separated in health services in Indonesia. Patient satisfaction is one of the important indicators that must be considered in providing health services. Service quality is an indicator of achieving patient satisfaction, including the role of health workers while planning health services, with the efficiency and effectiveness of health care providers being a key factor in the overall success of these services. Patients receiving BPJS at Tamalate Health Center in Makassar City were the subjects of this investigation, which aimed to identify the relationship between health worker performance and loyalty and patient satisfaction via service quality as a mediating variable. The Tamalate Health Center in Makassar City is the site of this quantitative study that employs a causal survey technique. A questionnaire was used as the tool. Path analysis is then used as the data analysis approach. Service quality for BPJS patients at Makassar City's Tamalate Health Center was shown to be directly impacted by health staff performance and loyalty. At Makassar City's Tamalate Health Center, BPJS patient satisfaction is directly impacted by the loyalty and performance of health workers. At the Tamalate Health Center in Makassar City, BPJS patients' satisfaction is indirectly affected by the performance of health workers via the level of service they get. For BPJS patients at the Tamalate Health Center in Makassar City, customer loyalty indirectly affects happiness via service quality.